Pengujian Negative Framing Dan Adverse Selection Sebagai Determinan Eskalasi Komitmen Dalam Keputusan Investasi - Anggraeni, Dewi; Rukmana, Risa (Universitas Patria Artha, 2020)
Commitment escalation refers to the tendency by a decision maker to persist or escalate his commitment to a series of failed actions. This study aims to analyze the effect of Negative Framing and Adverse Selection as Determinants of Commitment Escalation in Investment Decisions. Respondents who participated were 123 students majoring in Accounting and Management at the Tri Dharma Nusantara College of Economics who met the criteria, namely final semester students and had worked for certain companies to strengthen their decision-making abilities and had passed the entrepreneurship and Operational Management courses. This study was measured using a questionnaire and then analyzed using Multiple Linear Regression. The results of the research on Negative Framing and Adverse Selection have a significant positive effect on the Determinants of Commitment Escalation in Investment Decisions.